2015
DOI: 10.1016/j.ejmech.2014.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel substituted purine derivatives and identification of the cell death mechanism

Abstract: Novel 9-(substituted amino/piperazinoethyl)adenines (4-12), 6-(substituted piperazino/amino)purines (15-27), 9-(p-toluenesulfonyl/cyclopentyl/ethoxycarbonylmethyl)-6-(substituted amino/piperazino)purines (28-34, 36, 37, 38-41) were synthesized and evaluated initially for their cytotoxic activities on liver Huh7, breast T47D and colon HCT116 carcinoma cells. N(6)-(4-Trifluoromethylphenyl)piperazine derivative (17) and its 9-(p-toluene-sulfonyl)/9-cyclopentyl analogues (28, 36) had promising cytotoxic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In recent years, purine analogues, which are Hsp90 inhibitors, have entered clinical trials as drugs in the therapy of solid tumors and hematologic malignancies. 50 In our previous studies, 51,52 we have reported important cytotoxic activities of 9-(cyclopentyl/β-D-ribofuranosyl/para-toluenesulfonyl)-6-(4-substituted piperazino)purine analogs A, B, C ( Figure 2). In this work, we report the synthesis of new analogs of purines A, B, C as 9-(4-substituted benzyl)purines and evaluate their cytotoxic activities against liver (Huh7), colon (HCT116) and and breast (T47D) carcinoma cell lines.…”
Section: Introductionmentioning
confidence: 91%
“…In recent years, purine analogues, which are Hsp90 inhibitors, have entered clinical trials as drugs in the therapy of solid tumors and hematologic malignancies. 50 In our previous studies, 51,52 we have reported important cytotoxic activities of 9-(cyclopentyl/β-D-ribofuranosyl/para-toluenesulfonyl)-6-(4-substituted piperazino)purine analogs A, B, C ( Figure 2). In this work, we report the synthesis of new analogs of purines A, B, C as 9-(4-substituted benzyl)purines and evaluate their cytotoxic activities against liver (Huh7), colon (HCT116) and and breast (T47D) carcinoma cell lines.…”
Section: Introductionmentioning
confidence: 91%
“…For this reason, a large number of purine derivatives have been synthetized and their antitumor activity has been reported [20][21][22][23]. Compounds I [24] and II [25] (Figure 2) are examples of di-and tri-substituted purine derivatives that have already been tested against cancer cells. Both of these derivatives show anticancer activity on some cancer cell lines with sub-micromolar IC 50 values, and are therefore considered as potential drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, purine bases have been the subject of extensive research that led to the discovery of thousands of biological active compounds, including antineoplastic ones. [1][2][3][4][5][6] We synthesized a novel series of alkylated purines (1)(2)(3)(4)(5)(6)(7)(8)(9) with notable in vitro anti-proliferative activities, low toxicity and systemic distribution after oral administration in vivo. [1] The design of these compounds was based on the modifications of acyclic O,N-acetals, previously described by our research group as anti-proliferative agents.…”
Section: Introductionmentioning
confidence: 99%